Assessing Health Disparities in Digital Services and Technologies During and After the COVID-19 Pandemic: A Pooled Cross-Sectional Analysis Using HINTS Data - Shih HJ; Min H; Chang J (Patient Preference and Adherence)
Huan-Ju Shih,1 Hua Min,1 Jongwha Chang2 1Department of Health and Human Services, George Mason University, Fairfax, VA, USA; 2Department of Internal Medicine, School of Medicine, Wayne State University, Detroit, MI, USACorrespondence: Jongwha Chang, Wayne State University, School of Medicine, Department of Internal Medicine, Detroit, MI, 48201, USA, Tel +1313-966-9687, Email jochang@umich.eduIntroduction: Digital health techniques were adopted faster during COVID-19, but the gap remains. This study analyzes how the digital gap affected pandemic patient portal uptake during and after. Patient portals improve physician connections and patient health information access, increasing health outcomes. Digital divide—lack of internet, digital literacy, and SDOH—may inhibit fair adoption. One study found that the internet and IT affected people during and after the pandemic. Learn why this patient demographic uses online patient portals so much. Like finding demographic, socioeconomic, and behavioral characteristics that affect portal usage, specifically drivers and barriers for health-conscious patients. This project developed a health promotion model and implemented initiatives to increase patient portal use and reduce health inequities.Methods: In 2020 and 2022, we used Health Information National Trends Survey (HINTS) data. Patient portal use dominated. Our cross-sectional study assessed patient portal use and various predictors. Age, marital status, sex, mental health, education, income, urban/rural (urbanity), family size, trust, social media use, chronic condition, and health app use predict. We handled survey data collection biases with weighted analyses. Data was computed using survey weights for population representation. Logistic regression and weighted descriptive statistics utilized STATA SE 16.1.Results: Demographic, socioeconomic, and behavioral characteristics significantly affect online patient portal use. Portal usage is positively correlated with health app use, urbanity, higher income, sex, Asian/Native American race/ethnicity, and hospital trust. In addition, our data shows low adoption rates across the digital divide. Patients who trust others utilize patient portals, and previously established characteristics affect self-motivation for health improvement.Conclusion: Access obstacles and behavioral factors affect online patient portal adoption. Addressing the digital divide is crucial, but trust and self-motivation may improve patient portal utilization. Adopting health IT can improve patient participation and access to care, supporting equitable health outcomes.Keywords: mobile health, health disparity, healthcare policy, Post-SARS Cov2 care management